2021
DOI: 10.18805/lr-621
|View full text |Cite
|
Sign up to set email alerts
|

Cropping Systems of Fenugreek with Faba Bean to Reduce Broomrape Infestation 

Abstract: Background: Broomrape (Orobanche crenata Forsk.) is a major threat to faba bean and an important danger parasite. An intercropping is a necessity to curb the spread and progress of the parasite before it leads to much more economic losses. The current study was aimed to evaluate intercropping of fenugreek with faba bean under two plant densities of both crops on broomrape incidence to increase faba bean yield, land usage and economic return in heavy soil infestation of broomrape.Methods: This study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Under naturally infested soil conditions by broomrape, it could be observed that delaying sowing dates significantly increased the biological yield (ton/fed) in both seasons. These findings were consistent with those obtained by El-Degwy et al (2010), El-Ghareib et al (2019), and Abdel-Wahab and Eman (2021. Results in Table ( 6) clarified a significant differences among three faba bean cultivars in the biological yield (ton/fed) in both seasons.…”
Section: Biological Yield (Ton/fed)supporting
confidence: 92%
See 1 more Smart Citation
“…Under naturally infested soil conditions by broomrape, it could be observed that delaying sowing dates significantly increased the biological yield (ton/fed) in both seasons. These findings were consistent with those obtained by El-Degwy et al (2010), El-Ghareib et al (2019), and Abdel-Wahab and Eman (2021. Results in Table ( 6) clarified a significant differences among three faba bean cultivars in the biological yield (ton/fed) in both seasons.…”
Section: Biological Yield (Ton/fed)supporting
confidence: 92%
“…Consequently, faba bean plants grown under these treatments have low exposure to stress from the broomrape parasitic weeds, which reflects on plant vigor, formation of assimilates and its translocation from source to sink, allowing them to produce the highest number of pods/plant under these conditions. These results took the same trend as those recorded by Bakheit et al (2002), Ghalwash et al (2012), El-Mergawi andEl-Dabaa (2021), andAbdel-Wahab andEman (2021). The interaction between sowing dates and cultivars (S × C) was significant on the number of pods/plant in both seasons.…”
Section: Number Of Pods/plantsupporting
confidence: 86%
“…Furthermore, it is possible to scale more than one chip sets on the same substrate. There is no any issue in mounting component which is fabricated with different technologies, so it reduces losses and parasitic losses (5).…”
Section: Methodsmentioning
confidence: 99%
“…Where, = ( ) ( ) [5] Figure 5 illustrates the U-shape slotted patch antenna layout whose complete geometry is centered around U-shape slot whose positional variations are the deciding parameters of frequency of antenna design (15). Calculation of holes and their position is decided by trial and error method (16).…”
Section: Antenna Designmentioning
confidence: 99%
“…crenata crop allelopathic effect [94]. Using fenugreek in different plant densities and ridge widths, it was shown that two rows of faba bean (100% of sole cropping) on both sides of a wide ridge (120 cm width) with four rows of fenugreek (100% of sole cropping) in the middle of the ridge, could be an integrated control strategy to increase faba bean productivity, land usage and economic return whilst reducing broomrape infestation [95].…”
Section: No Information Providedmentioning
confidence: 99%